(untitled) (Scholars’ Journal, 2022)
In this research article the current learning practices to the students with physical disabilities are discussed. It is a qualitative study. The main objective of the study is to analyze current learning practices used for students with physical disabilities in Kailali district. Interview schedule and classed observation were the major tools for the collection of data in the study. The researcher chose case study as a research design. In this study, the organization is a case where physically disabled students stay and study. Among eight teachers three teachers were selected through Purposive sampling method. The data were collected from teachers who were teaching physically disabled students in school teaching. The findings of the study showed that the practice of teaching physically disabled students seemed to be difficult and challenging. The foremost reason behind this is the lack of disability-assistive infrastructure, parental support, social stigma, teachers training and awareness. Moreover, the findings revealed that teachers’ professionalism, engagement with students, planning for the lesson, inculcating the spirit of a creative and critical thinking and setting goals can prove instrumental to maximize students’ outcomes. The implication of the study is that the teachers should enhance special skills to deal with physically disabled students for their better performance.